Socratic as Mathematics Learning Application for Differential Equations Concept - Wanda Nugroho Yanuarto; Anton Jaelani; Joko Purwanto; Mohamad Ikram Zakaria (Program Studi Tadris Matematika IAIN Salatiga, 2021)
Technological improvements in the era of the Industrial Revolution 4.0 can be applied to learning mathematics as a medium of improving teacher performance. In addition, a pandemic situation forces teachers and students to implement online learning. One of the learning media that can help teachers in learning mathematics online is Socratic. The Socratic system generally consists of four basic components: acting humanely, thinking humanely, thinking rationally and acting rationally. For example, the Socratic can provide alternative solutions to the differential equations problems. Mathematics problems can be recorded by the Socratic through three main features:1) home screen, which is used to take pictures of solving the problem needed; 2) search results, the image that has been recorded will be searched for a solution through Socratic's artificial intelligence in internet database, and 3) an explanation, the search results that have been obtained, have their own explanation. Teachers and students as users may find the best solution for each explanation by the Socratic. Meanwhile, this study uses four stages of the literature review process:1) search for relevant literature, 2) evaluation and source selection, 3) identification of themes, and 4) outline of the structure of the writing. This paper systematically investigates the use of the Socratic as a technology application that can assist mathematical problems.